Implementation of Fuzzy Logic in Fish Dryer Design - Yanti, Nur; Nur, Taufik; Randis, Randis (ILKOM Jurnal Ilmiah, 2022)
The fish drying process aims to preserve fish, so as to reduce losses due to the spoilage process. There is sunlight, the drying process does not experience obstacles, however if it is raining, it will take a longer time, and give a smell effect that disturbs the surrounding environment for a relatively long time. Fish dryer designed to work automatically, aims to speed up drying time using fuzzy logic, thus minimizing rot and air pollution due to the smell of the fish drying process. The design of the tool used experimental methods through literature study as a source of study, planning and manufacturing of fish drying equipment consists of hardware using the Arduino Mega 2560 microcontroller, temperature sensor of DHT 22, load cell sensor, humidity sensor, fan, heating element and LCD and software using the Fuzzy Mamdani method. The results obtained are the weight of the fish that has undergone a drying process using an automatic drying device, namely 500 grams, indicating that the drying process is 50% of the initial weight of 1000 grams, with a drying time of 4.48 hours, while drying time by drying or manually takes 45 hours. Shows the control system using fuzzy logic on fish drying equipment, speed up the drying time about 10 hours faster than the drying time by drying in the sun. So that it can increase the amount of dry fish production, reduce the smell in the environment around the drying, because the fish are in the dryer closed.